Electric motors motor branch circuit protection - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
This interactive training unit is designed to familiarize trainees with the basic operation and maintenance of motor branch circuits. After completing this unit, trainees should be able to describe the components of a typical motor branch circuit, preventive maintenance procedures, and one way to troubleshoot a problem in a motor branch circuit.
Keywords: Electric motors; Electric controllers